Implikasi Aliran Filsafat Idealisme terhadap Praksis Pendidikan Agama Kristen - Go Heeng; Remegises Danial Yohanis Pandie; Yunardi Kristian Zega (STT Bala Keselamatan Palu, 2023)
Abstract: Philosophy of idealism in the praxis of Christian religious education focuses on developing spiritual awareness, building a relationship with God and strengthening basic religious values. Idealism also emphasizes the importance of recognizing the truth and understanding the essence of human existence. This can help in forming a positive mindset, making good decisions, and acting with integrity and responsibility. However, in practice not many understand the concept of philosophy of idealism, so that the practice of Christian religious education often ignores philosophical concepts that contribute to the process of improving Christian religious education itself. The method used in this research is literature study. The results of the study show that there are implications of the philosophy of idealism in the praxis of Christian religious education, namely the importance of understanding religious concepts, focusing on developing individual potential, prioritizing the learning process and prioritizing personal experience. Thus, the philosophy of idealism can be applied in the practice of Christian religious education by paying attention to spiritual values, character education, holistic education, and inclusive education. Abstrak: Filsafat idealisme dalam praksis pendidikan agama Kristen fokus pada pengembangan kesadaran spiritual, membangun hubungan dengan Tuhan dan memperkuat nilai-nilai agama yang mendasar. Idealisme juga menekankan pada pentingnya mengenali kebenaran dan memahami esensi keberadaan manusia. Hal ini dapat membantu dalam membentuk pola pikir yang positif, membuat keputusan yang baik, dan bertindak dengan integritas serta tanggung jawab. Namun, dalam praktiknya belum banyak yang memahami konsep filsafat idealisme, sehingga praksis pendidikan agama Kristen sering kali mengabaikan konsep-konsep filsafat yang punya sumbangsih bagi proses perbaikan pendidikan agama Kristen itu sendiri. Adapun metode yang digunakan dalam penelitian ini adalah studi pustaka. Hasil penelitian menunjukkan bahwa terdapat implikasi filsafat idealisme dalam praksis pendidikan agama Kristen yaitu pentingnya pemahaman konsep-konsep keagamaan, fokus pada pengembangan potensi individu, mengutamakan proses belajar dan mengutamakan pengalaman pribadi. Dengan demikian, filsafat idealisme dapat diterapkan dalam praksis pendidikan agama Kristen dengan memperhatikan nilai-nilai spiritual, pendidikan karakter, pendidikan holistik, dan pendidikan inklusif.